Journey : based on the true story of OR7, the most famous wolf in the West - Smith, Emma Bland (Little Bigfoot, an imprint of Sasquatch Books, 2016)
"A fictionalized account about a real wolf with the scientific name OR7 (the 7th radio-collared wolf in Oregon) that traveled from eastern Oregon to northern California--the first known wolf in the Golden State in 90 years"--